THE ROLE OF NAQSHBANDIYA VALUES IN SHAPING THE PERSONALITY OF THE TEACHER (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article presents mechanisms for improving students’ professional competence through the scientific heritage of the Naqshbandiya order, including methods of influence through values.